Light-emitting diode chip for improving polarization effect of quantum well light-emitting layer and preparation method of light-emitting diode chip

By inserting InxGa1-xN/GaN and GaN/AlyGa1-yN superlattice composite structures between the quantum well light-emitting layer and the P-type electron blocking layer, and adjusting the doping concentrations of In and Al, the problem of polarization effect in the quantum well structure is solved and the luminous efficiency of LEDs is improved by buffering energy level abrupt changes.

CN121099799APending Publication Date: 2025-12-09NANTONG TONGFANG SEMICON
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511210454.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-27
Publication Date
2025-12-09

AI Technical Summary

Technical Problem

The quantum confinement Stark effect and polarization electric field caused by lattice mismatch in the InGaN/GaN quantum well structure lead to a reduction in the quantum efficiency and light output of LEDs.

Method used

A composite structure of InxGa1-xN/GaN and GaN/AlyGa1-yN superlattices was inserted between the quantum well light-emitting layer and the P-type electron blocking layer. By adjusting the gradual change in the doping concentration of In and Al, the abrupt change in energy level was buffered, and the polarization effect was improved.

Benefits of technology

It effectively improves the polarization effect inside the quantum well, enhances the electron-hole radiative recombination efficiency, and improves the luminous efficiency of LEDs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121099799A_ABST
    Figure CN121099799A_ABST
Patent Text Reader

Abstract

The invention discloses a light-emitting diode chip for improving the polarization effect of a quantum well light-emitting layer and a preparation method of the light-emitting diode chip. Comprising a sapphire patterned substrate, a buffer layer, a defect barrier layer, an N-type gallium nitride layer, a current expansion layer, a stress release layer, a quantum well light-emitting layer, a polarization buffer layer, a P-type electron barrier layer, a P-type gallium nitride layer, a transparent conductive layer, an electrode layer and a protective layer which are sequentially arranged from bottom to top. The polarization buffer layer is arranged between the quantum well light-emitting layer and the P-type electron blocking layer, buffers energy level abrupt change, and improves the polarization effect. A composite structure of an In < x > Ga < 1-x > N / GaN superlattice and a GaN / Al < y > Ga < 1-y > N superlattice is inserted between the multi-quantum well layer and the electron blocking layer, mutation of energy level is buffered by adjusting gradient doping of In and Al, the polarization effect in quantum wells caused by high potential barriers of the electron blocking layer is effectively improved, and the luminous efficiency of the diode is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of LED chips, and in particular to a light-emitting diode chip with improved quantum well light-emitting layer polarization effect and its fabrication method. Background Technology

[0002] Currently, widely used gallium nitride-based blue-green light-emitting diodes (LEDs) typically employ InGaN / GaN quantum well / quantum barrier layers as the active region. High-quality InGaN quantum well layers and GaN quantum barrier layers are crucial for achieving high-efficiency, high-brightness LEDs. However, since the development of gallium nitride-based LEDs, the problems inherent in the InGaN / GaN multi-quantum-well structure have been a focus of researchers' efforts to improve. Firstly, the higher In content in the InGaN quantum well increases the lattice mismatch between the well layer and the GaN barrier layer, leading to a large piezoelectric field in the InGaN quantum well, resulting in the so-called quantum confinement Stark effect. The quantum confinement Stark effect reduces the coupling between the electron and hole wave functions in the quantum well, leading to a decrease in the quantum efficiency within the LED. Secondly, the large lattice mismatch in the quantum well causes the polarization electric field to bend the LED's bandgap, further reducing the LED's light output. Researchers have made significant progress in addressing these issues, achieving a luminous efficiency of 200-240 lm / W for blue LEDs. There are several main methods to mitigate the polarization effect of the active layer of a quantum well. The following are some commonly used fabrication techniques: 1) Using non-polar or semi-polar substrates. Non-polar (e.g., m-plane, a-plane) or semi-polar substrates can significantly reduce the polarization electric field; 2) Introducing layers opposite to the strain direction of the quantum well (e.g., growing AlGaN or InAlN strain compensation layers on both sides of the quantum well) to compensate for strain and counteract piezoelectric polarization; 3) Gradual quantum well composition. Adjusting the doping amount of In in the multi-quantum-well layers smooths the lattice mismatch and reduces the accumulation of polarization charge at the interface; 4) Reducing the thickness of the quantum well will relatively weaken the influence of the polarization electric field on the bandgap; 5) Inserting thin layers (AlN, Mg doped layers) near the quantum well layer to compensate for the polarization effect through interface charge. Summary of the Invention

[0003] Purpose of the invention: In order to solve the problems existing in the prior art, the present invention provides a light-emitting diode chip with improved polarization effect of quantum well light-emitting layer and its preparation method, which effectively improves the polarization effect inside the quantum well and further improves the light-emitting efficiency of the diode.

[0004] Technical Solution: This invention discloses a light-emitting diode chip for improving the polarization effect of a quantum well light-emitting layer. The light-emitting diode chip for improving the polarization effect of a quantum well light-emitting layer comprises, from bottom to top: a sapphire patterned substrate, a buffer layer, a defect blocking layer, an N-type gallium nitride layer, a current spreading layer, a stress relief layer, a quantum well light-emitting layer, a polarization buffer layer, a P-type electron blocking layer, a P-type gallium nitride layer, a transparent conductive layer, an electrode layer, and a protective layer; the polarization buffer layer is disposed between the quantum well light-emitting layer and the P-type electron blocking layer to buffer energy level abrupt changes and improve the polarization effect.

[0005] Furthermore, the polarization buffer layer material is In. x Ga 1-x N / GaN superlattice and GaN / Al y Ga 1-y The composite structure of the N superlattice; the In x Ga 1-x In the N / GaN superlattice, the In doping concentration gradually decreases, and the GaN / Al y Ga 1-y The Al doping concentration gradually increases in the N superlattice, which buffers the energy level rise from the quantum well emitting layer to the P-type electron blocking layer.

[0006] Furthermore, the stress relief layer is In δ The GaN / GaN superlattice structure contains trace amounts of In doping.

[0007] Furthermore, the quantum well light-emitting layer is an InGaN / GaN multi-quantum-well structure.

[0008] Furthermore, the P-type electron blocking layer is an electron blocking layer made of P-type AlGaN material.

[0009] This invention also discloses a method for fabricating a light-emitting diode chip with improved polarization effect of quantum well light-emitting layer, comprising the following steps: a) Prepare a patterned sapphire substrate and perform pre-cleaning; b) A buffer layer, a defect blocking layer, an N-type gallium nitride layer, a current spreading layer, a stress relief layer, a quantum well light-emitting layer, a polarization buffer layer, a P-type electron blocking layer, and a P-type gallium nitride layer are sequentially grown on the cleaned sapphire patterned substrate. c) Form a transparent conductive layer on the p-type gallium nitride layer; d) P-electrodes and N-electrodes are formed on the transparent conductive layer and the N-type gallium nitride layer, respectively, forming the electrode layer; e) A protective layer is formed on the electrode layer and the transparent conductive layer.

[0010] Furthermore, the preparation and pre-cleaning method of the sapphire patterned substrate in step a) is as follows: AlN material is deposited on the sapphire patterned substrate by sputtering technology, wherein the AlN material is part of the buffer layer; the sapphire patterned substrate with AlN material is placed in an MOCVD chamber, and hydrogen gas is introduced into the chamber environment at a high temperature to pre-clean the surface of the sapphire patterned substrate.

[0011] Furthermore, in step b), the growth buffer layer specifically comprises: a low-temperature GaN, a high-temperature GaN nucleation layer, and a high-quality three-dimensional GaN; the defect blocking layer is an undoped AlGaN defect blocking layer grown on the buffer layer; the N-type gallium nitride layer is a Si-doped N-type gallium nitride layer grown on the undoped AlGaN defect blocking layer; the current spreading layer is a low-concentration Si-doped gallium nitride current spreading layer grown on the N-type gallium nitride layer; the stress relief layer is a low-In-doped InGaN / GaN shallow well structure stress relief layer grown on the low-concentration Si-doped gallium nitride current spreading layer; the multi-quantum well light-emitting layer is an InGaN / GaN multi-quantum well light-emitting layer grown on the low-stress relief layer; the polarization buffer layer is a polarization buffer layer grown on the InGaN / GaN quantum well light-emitting layer; the electron blocking layer is a Mg-doped P-type AlGaN electron blocking layer grown on the polarization buffer layer; and the P-type gallium nitride layer is a Mg-doped P-type gallium nitride layer grown on the AlGaN electron blocking layer.

[0012] Furthermore, a polarization buffer layer is grown on the InGaN / GaN quantum well light-emitting layer structure, wherein the polarization buffer layer material is In. x Ga 1-x N / GaN superlattice and GaN / Al y Ga 1-y A composite structure of N superlattices, in which In x Ga 1-x The N / GaN superlattice growth period consists of 5 pairs, with x values ​​of 0.05 / 0.04 / 0.03 / 0.02 / 0.01, and a single layer of In... x Ga 1-x The thicknesses of N / GaN were 10~20Å and 20~50Å, respectively, and the growth temperature was 800~900℃; GaN / Al y Ga 1-y The N superlattice growth period consists of 4 pairs, with y values ​​of 0.04 / 0.06 / 0.08 / 0.1, forming a monolayer GaN / Al. y Ga 1-y The thicknesses of N were 20~50Å and 20~50Å, respectively, and the growth temperature was 900~950℃.

[0013] Furthermore, the specific preparation methods for steps c)-e) are as follows: 1) Perform MESA lithography on the prepared epitaxial wafer, select an appropriate etching depth according to the difference in epitaxial layer thickness, and etch out the N electrode platform; 2) A transparent conductive layer is deposited on the etched N-electrode platform epitaxial wafer. Then, the transparent conductive layer on the N-electrode platform region is etched away by photolithography, leaving only the transparent conductive layer on the P-type gallium nitride layer. The transparent conductive layer is made of indium tin oxide (ITO) with a thickness of 200 Å to 2000 Å. It can be deposited and grown by E-beam electron beam evaporation, sputter magnetron sputtering, or RPD reactive plasma deposition. 3) A metal electrode layer is deposited on the epitaxial wafer coated with a transparent conductive layer using an E-beam vapor deposition device. The material of the electrode layer is one or more alloy combinations of Cr / Al / Ti / Pt / Au. The electrode pattern is designed based on the principle of optimal current spread and minimal light shading effect. 4) A protective layer is deposited on the epitaxial wafer on which the electrode layer is formed. The protective layer material is SiO2 material, and the growth thickness is 500Å~5000Å. The SiO2 material is deposited using a PECVD device to finally obtain a light-emitting diode chip with improved polarization effect of quantum well light-emitting layer.

[0014] Beneficial effects: The present invention has the following advantages: (1) The present invention inserts In between the multi-quantum well layer and the electron blocking layer. x Ga 1-x N / GaN superlattice and GaN / Al y Ga 1-y The composite structure of the N superlattice buffers the abrupt change in energy levels by adjusting the gradual doping of In and Al. The potential barrier height of the polarization buffer layer in this composite structure shows a gradual trend, buffering the potential from the quantum well barrier height to the electron blocking layer barrier height, effectively improving the polarization effect inside the quantum well caused by the high barrier of the electron blocking layer. (2) In x Ga 1-x N / GaN superlattice and GaN / Al y Ga 1-y The potential barrier of the N superlattice composite structure has a slope, which is conducive to the effective injection of holes into the quantum well, thus improving the electron-hole radiative recombination efficiency and further enhancing the luminous efficiency of the diode. Attached Figure Description

[0015] Figure 1 This is a schematic diagram of the epitaxial layer structure of a light-emitting diode that improves the polarization effect of the quantum well light-emitting layer in a specific embodiment of the present invention; Figure 2 This is a schematic diagram of the structure of a light-emitting diode chip that improves the polarization effect of the quantum well light-emitting layer in a specific embodiment of the present invention.

[0016] Among them: 01-Sapphire patterned substrate, 02-Buffer layer, 03-Defect blocking layer, 04-N-type gallium nitride layer, 05-Current spreading layer, 06-Stress relief layer, 07-Quantum well light-emitting layer, 08-Polarization buffer layer, 09-P-type electron blocking layer, 10-P-type gallium nitride layer, 11-Transparent conductive layer, 13-P electrode, 14-N electrode, 12-Protective layer. Detailed Implementation

[0017] Please refer to Figure 1-2 As shown, the present invention provides a light-emitting diode chip with improved polarization effect of quantum well light-emitting layer and its fabrication method. The chip structure from bottom to top includes: sapphire patterned substrate 01, buffer layer 02, defect blocking layer 03, N-type gallium nitride layer 04, current spreading layer 05, stress relief layer 06, quantum well light-emitting layer 07, polarization buffer layer 08, P-type electron blocking layer 09, P-type gallium nitride layer 10, transparent conductive layer 11, P electrode 13, N electrode 14, and protective layer 12.

[0018] The polarization buffer layer 08 is disposed between the quantum well emitting layer 07 and the p-type electron blocking layer 09 to buffer energy level abrupt changes and improve the polarization effect. The polarization buffer layer 08 is made of In. x Ga 1-x N / GaN superlattice and GaN / Al y Ga 1-y The composite structure of the N superlattice; the In x Ga 1-x In the N / GaN superlattice, the In doping concentration gradually decreases, and the GaN / Al y Ga 1-y The Al doping concentration gradually increases in the N superlattice, which buffers the energy level rise from the quantum well emitting layer 07 to the P-type electron blocking layer 09.

[0019] The stress relief layer 06 is In δ The GaN / GaN superlattice structure contains trace amounts of In doping. The quantum well emitting layer 07 is an InGaN / GaN multi-quantum-well structure. The p-type electron blocking layer 09 is an electron blocking layer made of p-type AlGaN material.

[0020] In this embodiment, the following process flow is provided for the fabrication method of epitaxial wafers and chips of light-emitting diodes that improve the polarization effect of quantum well light-emitting layers.

[0021] 1) AlN material is deposited on a sapphire patterned substrate 01 by sputtering technology. The AlN material is part of the buffer layer 02 and has a thickness of 50~200 Å. The sputtering technology can obtain AlN material with good crystal quality. 2) The sapphire patterned substrate 01 coated with AlN material is placed in MOCVD and hydrogen gas is introduced into the cavity to perform high-temperature cleaning on the surface of the sapphire patterned substrate 01. 3) In the MOCVD equipment, a buffer layer 02 is further grown on the sapphire patterned substrate 01 coated with AlN material; the material of the buffer layer 02 is GaN, and the thickness is 100~500 Å; the growth temperature of the above GaN material in the MOCVD chamber is 500~600℃; then the temperature is increased to continue the two-dimensional growth of GaN nucleation layer, the growth temperature is 900℃, and the growth thickness is 0.5~1µm; then high-quality three-dimensional GaN is grown, the growth temperature is 1000℃, and the growth thickness is 0.5~1µm; 4) An AlGaN defect barrier layer 03 is grown on the high-temperature three-dimensional GaN in an MOCVD device; the Al doping content of the AlGaN material is 15%, the growth temperature is 1050℃, and the growth thickness is 200~400Å. 5) A Si-doped N-type gallium nitride layer 04 is grown on the defect barrier layer 03 in an MOCVD apparatus; the growth temperature is 1050℃, the growth thickness is 1.5~3µm, and the Si doping concentration is 5×10⁻⁶. 18 cm -3 ~5×10 19 cm -3 ; 6) In an MOCVD apparatus, a current spreading layer 05 is grown on the N-type gallium nitride layer 04. The current spreading layer 05 is a low-concentration Si-doped gallium nitride layer; its growth temperature is 1050℃, its thickness is 150~300nm, and its Si doping concentration is 5×10⁻⁶. 16 cm -3 ~5×10 17 cm -3 ; 7) In the MOCVD equipment, a stress relief layer 06 with a low In doping concentration of InGaN / GaN shallow well structure is grown on the current spreading layer 05. The growth temperature of the stress relief layer 06 of the shallow well structure is 900℃, where In is a trace dopant and the InGaN / GaN growth cycle is 6 pairs. The function of this shallow well structure is to alleviate the piezoelectric polarization effect caused by the lattice mismatch between the multi-quantum well layer InGaN and the epitaxial layer GaN. 8) In the MOCVD equipment, an InGaN / GaN multi-quantum-well light-emitting layer 07 is grown on the stress-relieving layer 06; the quantum-well light-emitting layer 07 is formed by alternating growth of well layer InGaN and barrier layer GaN, with a growth cycle of 5 to 15, and a growth temperature of 800℃. 9) A polarization buffer layer 08 is grown on the InGaN / GaN quantum well light-emitting layer in an MOCVD device. The polarization buffer layer 08 has an InGaN structure. x Ga 1-x N / GaN superlattice and GaN / Al y Ga 1-y A composite structure of N superlattices; in which In x Ga 1-x The N / GaN superlattice growth cycle consists of 5 pairs, with the In doping content gradually decreasing. The x values ​​are 0.05 / 0.04 / 0.03 / 0.02 / 0.01, respectively. The monolayer In... x Ga 1-x The thicknesses of N / GaN were 10~20Å and 20~50Å, respectively, and the growth temperature was 800~900℃; GaN / Al y Ga 1-y The N-type superlattice has 4 growth periods, with the Al doping concentration gradually increasing. The y values ​​are 0.04 / 0.06 / 0.08 / 0.1, respectively, for monolayer GaN / Al. y Ga 1-y The thicknesses of N were 20~50Å and 20~50Å, respectively, and the growth temperature was 900~950℃. 10) An electron blocking layer 09 of p-type AlGaN material with a thickness of 200~1000 Å and a Mg doping concentration of 5×10⁻⁶ is grown on the polarization buffer layer 08 in an MOCVD apparatus. 18 cm -3 ~5×10 19 cm -3 ; 11) A p-type gallium nitride layer 10 is grown on the p-type AlGaN electron blocking layer in an MOCVD apparatus; the thickness of the p-type gallium nitride layer 10 is 200~1000 Å, and the Mg doping concentration is 5×10⁹ Å. 19 cm -3 ~5×10 20 cm -3 At the end of the P-type gallium nitride layer 10 crystal growth, the epitaxial wafer is subjected to rapid thermal annealing in an MOCVD device, which is beneficial to the activation of Mg doping in the P-type gallium nitride material, thereby improving the ohmic contact characteristics of the P-type gallium nitride material; thus, an epitaxial wafer with a complete epitaxial structure and improved quantum well light-emitting layer 07 polarization effect is obtained. 12) After cleaning the prepared epitaxial wafer from the MOCVD cavity, the N-electrode platform is first etched using ICP dry etching. The etching depth of the N-electrode platform is 1μm~1.5μm. Specifically, the clean epitaxial wafer is homogenized, exposed, and developed in the yellow light region. The mask layer pattern of MESA is copied to the surface of the epitaxial wafer. Then, dry etching is performed using ICP equipment to etch the area not covered by the mask layer down to the N-GaN layer, thereby obtaining the mesa of the N-electrode and the dicing channels between the cores. After etching, the residual photoresist, i.e. the mask layer, is removed by cleaning.

[0022] 13) A transparent conductive layer 11 is deposited on the epitaxial wafer with the etched N-electrode platform. The transparent conductive layer 11 is indium tin oxide (ITO) material with a thickness of 200 Å to 2000 Å. The ITO transparent conductive film can be grown by E-beam electron beam evaporation, sputter magnetron sputtering, or RPD reactive plasma deposition. The appropriate evaporation method is selected according to the photoelectric characteristics requirements of the LED chip. In this embodiment, sputter magnetron sputtering is used to deposit the indium tin oxide (ITO) material. Sputter magnetron sputtering can obtain a dense ITO film with relatively stable resistance. Then, the film is homogenized, exposed, and developed in the yellow light area to obtain the required pattern on the transparent conductive layer 11. The ITO layer on the metal electrode area, the N-electrode mesa, and the chip dicing channel is removed by wet etching. After that, the residual mask layer on the surface is removed by cleaning.

[0023] 14) P electrode 13 and N electrode 14 are deposited on the P electrode mesa and N electrode mesa covered with ITO transparent conductive layer. The materials of P electrode 13 and N electrode 14 are alloy combinations of Cr / Al / Ti / Pt / Au. Specifically, the process involves homogenization, exposure, and development in the yellow light region to form the required electrode patterns on the P electrode mesa 13 and N electrode 14 platforms covered with ITO transparent conductive layer. Then, the metal film layers of the P electrode and N electrode are deposited using an electron beam evaporation device, followed by gold removal and adhesive removal.

[0024] 15) A protective layer 12 for the chip is deposited on the epitaxial wafer on which the electrode layer is formed. The protective layer 12 is made of silicon dioxide and is deposited using PECVD. The film thickness is 600 Å to 3000 Å. Specifically, the silicon dioxide protective layer 12 is first deposited using PECVD equipment. Then, homogenization, exposure, and development are performed in the yellow light region to form the required protective layer pattern on the wafer surface (the mask layer exposes the P electrode 13 and N electrode 14 areas). The silicon dioxide protective layer material on the P electrode 13 and N electrode 14 is then removed by wet etching, followed by resist removal and cleaning. Finally, a light-emitting diode chip with improved N electrode current crowding effect is obtained.

[0025] This invention employs a composite polarization buffer layer 08, which buffers abrupt energy level changes by adjusting the gradual doping of In and Al. The barrier height of this composite polarization buffer layer 08 exhibits a gradual trend, buffering the transition from the quantum well barrier height to the electron blocking layer barrier height, effectively improving the polarization effect inside the quantum well caused by the high barrier of the electron blocking layer. On the other hand, this In… x Ga 1-x N / GaN superlattice and GaN / Al y Ga 1-y The potential barrier of the N superlattice composite structure has a slope, which is conducive to the effective injection of holes into the quantum well, thus improving the electron-hole radiative recombination efficiency and further enhancing the luminous efficiency of the diode.

Claims

1. A light-emitting diode chip with improved polarization effect of quantum well light-emitting layer, characterized in that... The structure comprises, from bottom to top, the following layers arranged in sequence: a sapphire patterned substrate, a buffer layer, a defect blocking layer, an N-type gallium nitride layer, a current spreading layer, a stress relief layer, a quantum well light-emitting layer, a polarization buffer layer, a P-type electron blocking layer, a P-type gallium nitride layer, a transparent conductive layer, an electrode layer, and a protective layer; the polarization buffer layer is disposed between the quantum well light-emitting layer and the P-type electron blocking layer to buffer energy level abrupt changes and improve the polarization effect.

2. The light-emitting diode chip with improved polarization effect of quantum well light-emitting layer according to claim 1, characterized in that: The polarization buffer layer material is In. x Ga 1-x N / GaN superlattice and GaN / Al y Ga 1-y The composite structure of the N superlattice; the In x Ga 1-x In the N / GaN superlattice, the In doping concentration gradually decreases, and the GaN / Al y Ga 1-y The Al doping concentration gradually increases in the N superlattice.

3. The light-emitting diode chip with improved polarization effect of quantum well light-emitting layer according to claim 1, characterized in that: The stress relief layer is In δ The GaN / GaN superlattice structure contains trace amounts of In doping.

4. The light-emitting diode chip with improved polarization effect of quantum well light-emitting layer according to claim 1, characterized in that: The quantum well light-emitting layer is an InGaN / GaN multi-quantum-well structure.

5. The light-emitting diode chip with improved polarization effect of quantum well light-emitting layer according to claim 1, characterized in that: The P-type electron blocking layer is an electron blocking layer of P-type AlGaN material.

6. A method for fabricating a light-emitting diode chip with improved polarization effect of quantum well light-emitting layer as described in any one of claims 1-5, characterized in that... Includes the following steps: a) Prepare a patterned sapphire substrate and perform pre-cleaning; b) A buffer layer, a defect blocking layer, an N-type gallium nitride layer, a current spreading layer, a stress relief layer, a quantum well light-emitting layer, a polarization buffer layer, a P-type electron blocking layer, and a P-type gallium nitride layer are sequentially grown on the cleaned sapphire patterned substrate. c) Form a transparent conductive layer on the p-type gallium nitride layer; d) P-electrodes and N-electrodes are formed on the transparent conductive layer and the N-type gallium nitride layer, respectively, forming the electrode layer; e) A protective layer is formed on the electrode layer and the transparent conductive layer.

7. The method for fabricating a light-emitting diode chip with improved polarization effect of quantum well light-emitting layer according to claim 6, characterized in that: The preparation and pre-cleaning method of the sapphire patterned substrate in step a) is as follows: AlN material is deposited on the sapphire patterned substrate by sputtering technology, wherein the AlN material is part of the buffer layer; A sapphire patterned substrate coated with AlN material is placed in an MOCVD chamber, and hydrogen gas is introduced into the chamber to pre-clean the surface of the sapphire patterned substrate.

8. The method for fabricating a light-emitting diode chip with improved polarization effect of quantum well light-emitting layer according to claim 6, characterized in that: In step b), the growth buffer layer specifically comprises: a low-temperature GaN layer, a high-temperature GaN nucleation layer, and a high-quality three-dimensional GaN layer; the defect blocking layer is an undoped AlGaN defect blocking layer grown on the buffer layer; the N-type gallium nitride layer is a Si-doped N-type gallium nitride layer grown on the undoped AlGaN defect blocking layer; the current spreading layer is a low-concentration Si-doped gallium nitride current spreading layer grown on the N-type gallium nitride layer; the stress relief layer is a low-In-doped InGaN / GaN shallow well structure stress relief layer grown on the low-concentration Si-doped gallium nitride current spreading layer; the multi-quantum well light-emitting layer is an InGaN / GaN multi-quantum well light-emitting layer grown on the low-stress relief layer; the polarization buffer layer is a polarization buffer layer grown on the InGaN / GaN quantum well light-emitting layer; the electron blocking layer is a Mg-doped P-type AlGaN electron blocking layer grown on the polarization buffer layer; and the P-type gallium nitride layer is a Mg-doped P-type gallium nitride layer grown on the AlGaN electron blocking layer.

9. The method for fabricating a light-emitting diode chip with improved polarization effect of quantum well light-emitting layer according to claim 8, characterized in that: A polarization buffer layer is grown on the InGaN / GaN quantum well light-emitting layer structure, wherein the polarization buffer layer material is In. x Ga 1-x N / GaN superlattice and GaN / Al y Ga 1-y A composite structure of N superlattices, in which In x Ga 1-x The N / GaN superlattice growth period consists of 5 pairs, with x values ​​of 0.05 / 0.04 / 0.03 / 0.02 / 0.01, and a single layer of In... x Ga 1-x The thicknesses of N / GaN were 10~20Å and 20~50Å, respectively, and the growth temperature was 800~900℃; GaN / Al y Ga 1-y The N superlattice growth period consists of 4 pairs, with y values ​​of 0.04 / 0.06 / 0.08 / 0.1, forming a monolayer GaN / Al. y Ga 1-y The thicknesses of N were 20~50Å and 20~50Å, respectively, and the growth temperature was 900~950℃.

10. The method for fabricating a light-emitting diode chip with improved polarization effect of quantum well light-emitting layer according to claim 6, characterized in that: The specific preparation methods for steps c)-e) are as follows: 1) Perform MESA lithography on the prepared epitaxial wafer, select an appropriate etching depth according to the difference in epitaxial layer thickness, and etch out the N electrode platform; 2) A transparent conductive layer is deposited on the etched N-electrode platform epitaxial wafer. Then, the transparent conductive layer on the N-electrode platform region is etched away by photolithography, leaving only the transparent conductive layer on the P-type gallium nitride layer. The transparent conductive layer is made of indium tin oxide (ITO) with a thickness of 200 Å to 2000 Å. It can be deposited and grown by E-beam electron beam evaporation, sputter magnetron sputtering, or RPD reactive plasma deposition. 3) A metal electrode layer is deposited on the epitaxial wafer coated with a transparent conductive layer using an E-beam vapor deposition device. The material of the electrode layer is one or more alloy combinations of Cr / Al / Ti / Pt / Au. The electrode pattern is designed based on the principle of optimal current spread and minimal light shading effect. 4) A protective layer is deposited on the epitaxial wafer on which the electrode layer is formed. The protective layer material is SiO2 material, and the growth thickness is 500Å~5000Å. The SiO2 material is deposited using a PECVD device to finally obtain a light-emitting diode chip with improved polarization effect of quantum well light-emitting layer.

Citation Information

Cited By

  • Blue-green LED epitaxial wafer and preparation method thereof

    CN121419405A